Pengaruh Motivasi dan Sarana Belajar Online Terhadap Kemandirian Belajar Mahasiswa FEB Institut Asia di Masa Pandemi Covid-19 - Risa Santoso (Jurnal Pendidikan Ekonomi, 2021)
Since the implementation of the lockdown (PSBB) policy in Indonesia, the student learning process in all levels of education in Indonesia have been carried out online. This has also been the case at the Business and Economic Faculty of Asia Institute, Malang. All of the students had to study from home (SFH) and interact with lecturers using online media such as Google Classroom, WhatsApp Group, Google Meet, Zoom and even application such as Discord using a laptop or a smartphone. Online learning during the Covid-19 pandemic became the only option to continue learning. Interestingly, online learning asserts high student independence. The purpose of this study was to determine the impact of online learning on students’ motivation and (learning) independence in the Faculty of Business and Economics of Asia Institute of Technology and Business, Malang. A total of 701 students were selected as respondents using simple random sampling technique. Data were collected through 5-point Likert scale questionnaires, then processed and analyzed using SEM-PLS analysis with SmartPLS 3.3.2 software. The results showed that both motivation and learning facilities were positively and significantly effected on student learning independence. The higher the motivation and the more complete, effective, and quality learning facilities, the higher the student's learning independence is. The main obstacle in the learning process is the lack of internet connection/ data signals in several areas where students live, which makes online lectures laggard and less attractive. It is suggested for further research to investigate and analyze the mediating role of motivation in the relationship between learning facilities and student learning independence.DOI: https://dx.doi.org/10.17977/UM014v14i12021p25